FATWA IN THE DIGITAL ERA: COMMUNICATION STRATEGY OF THE MUI IN DISSEMINATING THE UANG PANAI FATWA IN SOUTH SULAWESI - Azka, Ibnu; Nida, Sairatun; Rizki, Agam Muhammad; Baldan Haramain, Fathur (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
The understanding that emerges from some Bugis Makassar people about the meaning of dowry and Uang Panai' is still much wrong. So that it creates a lot of inequality, Uang Panai' is a condition that exceeds the dowry position. Therefore, the Indonesian Ulama Council of South Sulawesi issued a fatwa Uang Panai' to explain the position of Uang Panai' in Islam. This study aims to discuss how the South Sulawesi MUI uses a communication strategy in disseminating fatwa on Uang Panai' in the digital era. The method used in this research is field research with a qualitative descriptive phenomenological approach. The subject of this research is the management of the South Sulawesi Indonesian Ulama Council. Data collection techniques through observation, in-depth interviews and documentation. The main question of this research is how the communication strategy used by the South Sulawesi MUI in disseminating the Uang Panai' fatwa and why the South Sulawesi MUI uses digital media to disseminate the Uang Panai' fatwa. The results of this study indicate that the South Sulawesi MUI is able to accommodate two communication strategies in disseminating the Uang Panai' fatwa in the digital era.